Experiment on New Configuration of Hybrid Offshore T-junction to Remove Liquid Carryover - Arsad, Naidatul Zamrizam (2018)
T-junction commonly used by majority of oil/gas industries nowadays. The main function is for separation of gas. When gas coming from production header, it will split the gas that will be used for downstream instrumentation. Sometimes, the T-junction may experience excessive liquid carryover when slug flow develops in the main pipe. This will cause problem such as platform trips. Besides, they need to drain out the unnecessary liquid that accumulated in downstream equipment. Because of that, a new configuration of T-junction is introduced with additional extended tank at the branch arm which work as a separator, there is a vertical branch for flowing back to horizontal pipe. So that the gas can flows to the gas pipeline without contain any excessive liquid. This idea is to investigate experimentally its capability to minimize the liquid carryover under slug flow condition. Many study of two-phase flow separation have been done by using T-junction that nearly same configuration. However, there is no further study of it by adding additional pipe with geometrical enlargement of the tube cross-sectional area of the side arm. At the end of this thesis, the complication of phase separation in two-phase flow can be overcome to create better separation efficiency and to be apply in the pipeline system of oil and gas industries.